Estrogen receptor α promotes Cav1.2 ubiquitination and degradation in neuronal cells and in APP/PS1 mice. Issue 4 (22nd April 2019) - Lai, Yu‐Jie; Zhu, Bing‐Lin; Sun, Fei; Luo, Dong; Ma, Yuan‐Lin; Luo, Bio; Tang, Jing; Xiong, Ming‐Jian; Liu, Lu; Long, Yan; Hu, Xiao‐Tong; He, Ling; et al.
Abstract: Cav1.2 is the pore‐forming subunit of L‐type voltage‐gated calcium channel (LTCC) that plays an important role in calcium overload and cell death in Alzheimer's disease. LTCC activity can be regulated by estrogen, a sex steroid hormone that is neuroprotective. Here, we investigated the potential mechanisms in estrogen‐mediated regulation of Cav1.2 protein. We found that in cultured primary neurons, 17β‐estradiol (E2) reduced Cav1.2 protein through estrogen receptor α (ERα). This effect was offset by a proteasomal inhibitor MG132, indicating that ubiquitin–proteasome system was involved. Consistently, the ubiquitin (UB) mutant at lysine 29 (K29R) or the K29‐deubiquitinating enzyme TRAF‐binding protein domain (TRABID) attenuated the effect of ERα on Cav1.2. We further identified that the E3 ligase Mdm2 (double minute 2 protein) and the PEST sequence in Cav1.2 protein played a role, as Mdm2 overexpression and the membrane‐permeable PEST peptides prevented ERα‐mediated Cav1.2 reduction, and Mdm2 overexpression led to the reduced Cav1.2 protein and the increased colocalization of Cav1.2 with ubiquitin in cortical neurons in vivo. In ovariectomized (OVX) APP/PS1 mice, administration of ERα agonist PPT reduced cerebral Cav1.2 protein, increased Cav1.2 ubiquitination, and improved cognitive performances. Taken together, ERα‐induced Cav1.2 degradation involved K29‐linked UB chains and the E3 ligase Mdm2, which might play a role in cognitive improvement in OVX APP/PS1 mice. Abstract : Activation of ER‐alpha by PPT promotes Mdm2 association with Cav1.2. The subsequent Cav1.2 degradation by UPS involves K29‐linked UB chains and the PEST motif. In APP/PS1 mice, the reduced Cav1.2 may contribute to ER‐alpha‐induced cognitive improvement.